MANAJEMEN TALENTA BERBASIS AI (ARTIFICIAL INTELLIGENCE) DALAM MENINGKATKAN KOMPETENSI SUMBER DAYA MANUSIA (SDM) PADA BANK WAKAF MIKRO MAWARIDRUSSALAM KECAMATAN BATANG KUIS - Suhaila Husna Samosir; Mutawaqil Bilah Tumanggor; Muhammad Radian Syah; Riska Dwi Ananda; Maulida Syahputri (Journal Economic Management and Business, 2026)
Artificial Intelligence (AI) has become one of the most influential technological innovations in the digital era, significantly transforming various sectors, including human resource management. AI technology enables organizations to analyze data rapidly, identify patterns, and support automated decision-making processes, thereby improving employee competency development and talent management effectiveness. The implementation of AI in talent management allows Human Resources (HR) departments to identify employee potential more accurately and design personalized development programs. However, despite its benefits, AI adoption also presents challenges such as algorithmic bias and data privacy issues that may affect employee trust and the credibility of HR management. This research aims to analyze employee competency development in relation to talent management through the application of AI technology. The study applies a literature review approach, followed by interviews, Focus Group Discussions (FGD), and questionnaire development to identify research gaps and gain deeper insights. The expected outputs include scientific publications in accredited national journals and an ISBN-registered book, while the planned Technology Readiness Level (TRL) is at Level 1, focusing on the fundamental understanding of AI technology in talent management.